PENGARUH UANG ELEKTRONIK, SUKU BUNGA, DAN INFLASI TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA TAHUN 2015.I – 2023.IV - NURFAJRIRAHMA SABARINA; TAUFIQ CHAIDIR; IRWAN SURIADI (Universitas Mahasaraswati K. Mataram, 2024)
This study aims to test and analyze the effect of electronic money, interest rates, and inflation on economic growth in Indonesia in 2015.I-2023.IV. The type of research used is explanatory research. The research data source is secondary time series data in quarterly form, namely the first quarter of 2015 to the fourth quarter of 2023. The analysis model used is multiple linear regression analysis. Based on the results of partial hypothesis testing, it is concluded that the electronic money variable, and interest rates have no significant effect, while the inflation variable has a significant effect on economic growth. Simultaneously, the variables of electronic money, interest rates, and inflation simultaneously have a significant effect on economic growth. The acceleration of digital transactions should be accompanied by the availability of adequate infrastructure and simplify business regulations and increase market confidence so as to encourage economic growth.